Plasma ω-3 and ω-6 PUFA Concentrations and Risk of Atrial Fibrillation: The Multi-Ethnic Study of Atherosclerosis. Issue 6 (9th March 2021) - Garg, Parveen K; Guan, Weihua; Nomura, Sarah; Weir, Natalie; Karger, Amy B; Duprez, Daniel; Heckbert, Susan R; Tsai, Michael Y
ABSTRACT: Background: Current literature examining the prospective relation of circulating omega-3 (n–3) and omega-6 (n–6) PUFAs and atrial fibrillation (AF) is limited to predominantly white populations. Objectives: We investigated the association of circulating n–3 and n–6 PUFAs with incident AF in participants from the Multi-Ethnic Study of Atherosclerosis. Methods: A total of 6229 participants (mean age = 62 y; 53% female; 39% white, 27% black, 22% Hispanic, and 12% Chinese) who were free of baseline AF and with plasma phospholipid PUFAs measured at baseline using GC were prospectively followed for the development of AF. Incident AF was ascertained using International Classification of Diseases-9 codes from hospital discharge records and Medicare claims data with follow-up through 2014. Multivariable Cox proportional hazards regression analysis was performed to determine the risk of incident AF. Results: During a median follow-up of 12.9 y, 813 (13%) participants developed AF. Each higher SD increment in arachidonic acid (AA; 20:4n–6) concentrations was associated with an 11% decreased risk of incident AF (HR: 0.89; 95% CI: 0.82, 0.96). Similarly, higher overall n–6 PUFA concentrations were also associated with a reduced AF risk (HR per SD increment: 0.93; 95% CI: 0.87, 1.00). Although no significant overall associations were observed for any individual n–3 PUFAs, higher circulating concentrations of DHA (22:6n–3) and EPA (20:5n–3) were associated with a decreased AF risk in blacks and Hispanics (DHA only) but not whites or Chinese Americans. Conclusions: In a multiethnic cohort of individuals free of baseline cardiovascular disease, higher plasma concentrations of n–6 PUFAs, particularly AA, were associated with a reduced risk of incident AF. Important differences in AF risk were also noted across race/ethnicity for the n–3 PUFAs DHA and EPA.